Prototyping Revisited: - design with users in a cooperative setting - Bødker, Susanne (DAIMI Report Series, 1987)
In this paper, prototyping will be discussed from the point-of-view of user/designer cooperation in design. Active user participation in systems design is a way of improving the quality of the design process as well as the product - a computer application in use. To participate actively in design, users must be allowed to experience the future use situation in the design process. Various prototyping methods seem to offer valuable help in this process. Cooperation between users and designers, the mutual learning process, and hands-on experiences to reveal the triggering of proper operations is, however, only one side of the epistemological interests behind prototyping. At the same time, the practical solutions of different approaches are to some extent applicable but it is perhaps a good idea to reconsider the concept from the perspective of cooperation between users and professional designers.